G282(P) Snippets: Paediatric Blogging as an educational tool. (7th April 2014) - Glenday, EJS; Mathew, A; Roddham, M
Abstract : Aim: This abstract demonstrates how departments can address the limitations posed by the European Working Time Directive (EWTD) and shift based patterns by utilising the Internet as a forum to post reviews of journal articles and form a virtual journal club. Introduction: The EWTD and resultant shift based patterns have led to the erosion of team-based structures within the NHS. This has had a demonstrable impact on trainees' access to educational meetings including journal clubs and has reduced the opportunities for professional dialogue between clinicians. Knowledge can be gained from access to educational resources alongside face-to-face contact. The Internet is an obvious avenue to exploit as an educational forum in today's technology-driven world. Methods: We established 'Snippets', a paediatric blog in February 2012 to respond to this educational gap using open-access software at http://www.wordpress.com . The blog is managed by collaboration between library services in several hospital trusts and enables direct links to ascribed journal articles. The blog has tags linking similar postings, highlighting those of particular relevance to individual clinicians. It provides links to journal articles, external websites, guidelines and presentations. Results: The blog has had 65 postings in 22-months i.e. an average of 3 posts per month (Figure 1 ). Monthly viewing of the blog rose between 2012 and 2013 (Figure 2 ). This may be skewed downwards as some people receive a link to blog-postings in their email and do not directly visit the website. 22 different contributors have posted on 'Snippets', the majority being Consultants (Figure 3 ). Posting comments on the blog has proved to be difficult with Trust IT systems blocking such activity. Trust librarian's have been able to circumvent this, but this conduit has discouraged users from sending comments on for later posting. In the 22 months of this blog there have been only 25 comments posted by 8 commentators. Conclusion: This blog demonstrates how the Internet can be used to enable a network of multi-professionals to participate in collaborative learning. The virtual learning club we have developed has bridged the gap of distance and restricted working hours and has benefitted a community of practitioners.